Blindsighted eaudiobook - Slaughter, Karin (Grant County, 2004)
Don't miss the next Will Trent thriller, This Is Why We Lied, coming this August! From New York Times bestselling author Karin Slaughter, the first novel in her acclaimed Grant County Series. A small Georgia town erupts in panic when a young college professor is found brutally mutilated in the local diner. But it's only when town pediatrician and coroner Sara Linton does the autopsy that the full extent of the killer's twisted work becomes clear. Sara's ex-husband, police chief Jeffrey Tolliver, leads the investigation—a trail of terror that grows increasingly macabre when another local woman is found crucified a few days later. But he's got more than a sadistic serial killer on his hands, because the county's only female detective, Lena Adams—the first victim's sister—wants to serve her own justice. But it is Sara who holds the key to finding the killer. A secret from her past could unmask the brilliantly malevolent psychopath... or mean her death.